The effect of work-family conflict, work-life balance on employee performance with job stress as mediation in employees of the directorate general of health personnel of the ministry of health of the republic of Indonesia. - Mutiara, Mira Weningtyas; Mudjijah, Slamet (Jurnal Mantik, 2025)
This study examines the effect of work-family conflict and work-life balance on employee performance with job stress as a mediating variable in employees of the Directorate General of Health Personnel of the Ministry of Health of the Republic of Indonesia. The main problem identified is employees' challenges in managing their time and roles at work and personal life, which results in increased stress and decreased performance. The purpose of this study is to explore how work-family conflict and work-life balance affect employee performance, considering the role of job stress as a mediator. The study used quantitative methods with an associative approach, involving 500 employees of the Directorate General of Health Personnel in 2023. The results showed that work-family conflict has a significant effect on job stress (t-statistic 4.928) and employee performance (t-statistic 3.649). Work-life balance does not have a significant direct effect on performance (t-statistic 1.561), but affects performance through the mediation of job stress (t-statistic 2.599). Job stress proved to be an important mediator that affects the relationship between work-family conflict, work-life balance, and employee performance